Analisis Yuridis Pembatalan Hak Kepemilikan Atas Tanah yang Didasarkan pada Tindakan Hibah Lisan - Renaldo, Edward (Universitas Ekasakti, 2023)
Certificate can be sued in court for cancellation. Both civil and criminal verdict essentially does not involves administration in certificate issuance, but involves the authenticity in certificate issuance towards a piece of land proven with certificate, so that although registered as freehold title according to the decree that has acquired permanent legal force proven its issuance were using wrong rights and had been done by unrightful person, therefore the certificate was legally defective and could be cancelled. This research purposes is to analyze rights of ownership cancellation from legally defective rights (verbal grant) according to UUPA and KUHPerdata. Results shown that Act Number 5 Year 1960 and the enforcement regulation has given a collateral and protection for land of rights holder that essentially from another person who shifted their rights with the real holder not knowing, therefore the certificate can be sued for cancellation in court.